عقود التوريد.. رؤية فقهية جديدة - عبد الرحمن اجَّاه, أبُّوه (جامعة الوادي - University of Eloued, 2021)
لا شك أن عقود التوريد أصبحت حاجة ماسة؛ لا غنى للأفراد والدول عنها، والصيغة التي تتم بها الآن فيها مخالفات شرعية كابتداء الدين بالدين، وهو من بيع الدين المجمع على حرمته؛ لذلك اختلف فيها العلماء المعاصرون: فمجمع الفقه الإسلامي الدولي ذهب إلى عدم جوازها، ما لم تتوفر فيها شروط السلم أو الاستصناع. وفي القول بحرمتها ما فيه من الحرج والمشقة؛ لذلك ذهب بعض العلماء إلى القول بجوازها للضرورة، ولكنهم – في سبيل ذلك- لجأوا إلى تأويلات متكلفة، منها محاولة التشكيك في صحة الإجماع على منع بيع الدين بالدين، ومنها دعوى أن عقد التوريد ليس عقدا، وإنما هو وعد، إلا أنهم واجهتهم مشكلة أن عقد التوريد ملزم للطرفين؛ وقد تفرقوا في الجواب عن هذا الإشكال طرائق قددا، يجمعها أنها متكلفة غير مقنعة! وهذه الدراسة محاولة لتقديم رؤية فقهية جديدة، تمثل في اقتراح حل فقهي يوصل إلى القول بجواز عقد التوريد، من غير خرقٍ للإجماع، ولا لجوءٍ إلى تأويلات متكلفة تخالف الأصول وتكسر القواعد، وبذلك يحقق المطلوب، مع البعد عن المحظور الشرعي؛ وذلك بتحقيق المقصد الشرعي من التيسير والتخفيف. Summary of the research: There is no doubt that supply contracts have become an urgent need. It is indispensable for individuals and states, and the formula in which Sharia violations are now taking place, such as the initiation of religion into religion, and it is from the sale of religion unanimously inviolable. Therefore, contemporary scholars disagreed about it: The International Islamic Fiqh Academy argued that it is not permissible, as long as the conditions for salam or istisna 'are not met. And in saying that it is prohibited, it contains embarrassment and hardship. Hence, some scholars have argued that it is permissible for necessity, but - for that - they resorted to costly interpretations, including trying to question the validity of the consensus on preventing the sale of debt for debt, and including the claim that the supply contract is not a contract, but rather a promise, but they faced a problem that a contract The supply is binding on both parties; They have dispersed in the answer to this problem of predatory methods, which are combined by being pretentious and unconvincing! This study is an attempt to present a new jurisprudential vision, represented in proposing a jurisprudential solution that leads to the statement that the supply contract is permissible, without breaching consensus, nor resorting to pretentious interpretations that violate the principles and break the rules, and thus achieve the required, while avoiding the legal forbidden. And by achieving the legitimate purpose of facilitation and mitigation.
مقال في مجلة الشهاب بجامعة الوادي
Keywords: توريد، رؤية فقهية جديدة، عقود